ΑΓΩΝ ΑΟΓΩΝ en Heracles de Eurípides, vv. 140-251 (Argos, 2025)
Greek tragedies display an extraordinary formal and thematic variety as regards the composition of άγώνες. Eurípides' mastery and charm are revealed by skillful transference of rhetoric techniques and contemporary sophistic arguments into the mythical scene. The present paper aims to study in Eurípides' Heracles (422 b.C.) the structures of ρήσεις of its unusual άγών between Lycus and Amphitryon (140-251), in order to apply the precepts of classical rhetoric, which strongly influenced Euripides, as well as establishing the dramatic functional character of formal debate for the resolution of the tragedy.
Keywords: tragedy; Euripides; Heracles; rethoric; agon logon